The Formation of the Legal Facts Theory in the Context of the Development of Legal Science - Shafalovich, Hanna (Teisė, 2021)
This article reveals misconceptions in the study of the theory of legal facts in Roman law studies . The use of an institutional approach in Roman law studies led to the conclusion that there are no elements of the legal facts theory in Roman jurisprudence. Using a historical and theoretical approach, the author concluded that there was a developed system of legal facts in Ancient Rome and a system of logical and stable concepts of the legal facts theory formed at the level of the concept, which was accepted and developed by the subsequent legal science.